Postać Elżbiety Batory w historiografii - Szabelski, Adam (Poznańskie Towarzystwo Przyjaciół Nauk, 2014)
The aim of the paper is to present the figure of Elisabeth Bathory as it is shown in historiography and to confront the myths surrounding her person with the findings of the researchers, especially Hungarian scholars who studied her life. It has been shown that Elisabeth Bathory fell victim to the plot of the palatine György Turzó, probably instigated by the court in Vienna. Unfortunately, Polish historians have so far neglected to address this issue in their research.
THE FIGURE OF ELISABETH BATHORY IN HISTORIOGRAPHY
The article presents the state of research concerning the figure of Elisabeth Bathory. According to the popular opinion, the woman was considered a vampire or a mentally deranged person who murdered almost three hundred women of noble blood and peasants. Unfortunately, Polish historians have so far failed to address this issue. Meanwhile, in the course of long-running studies, Hungarian historiography has demonstrated that Elisabeth Bathory fell victim to the plot of palatine György Turzó, which was probably instigated by the court in Vienna. The theories relating to the causes of accusations leveled against the magnate include Habsburg intention to take over the strategic castle of Dévény, seizure of the estate of the Nádasdy family or actions against a relative of Elisabeth’s and at the same time a prince of Transylvania, Gabriel Bathory. The greatest credit due to Hungarian historiography is rehabilitation of the name of Elisabeth Bathory and critical verification of the injurious legend, since the woman was never accused of vampirism but of acts of criminal nature. It has also been proved that her imprisonment was illegal and founded on trumped up charges, while the actual trial had never taken place.
Keywords: ELISABETH BATHORY; HISTORY OF HUNGARY; RÓD NÁDASDY; GYÖRGY TURZÓ